Hubungan Antara Keterampilan Perawat Dalam Melaksanakan Bedside Handover Dengan Keselamatan Pasien Di Rumah Sakit - Ismuntania; Indah Nursanti; Khairunnisa Batubara; Rinawati; Rahmat Ali Putra Harahap (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
The skill of performing bedside handover is a major strength during bedside handover, because competent skills lead to the assurance of more accurate and up-to-date information regarding the patient's condition, which will affect the degree of patient safety. This study aims to determine the relationship between nurses' skills in performing bedside handover and patient safety. The research design is explanatory research with a cross-sectional approach. The population is all nurses working in the inpatient ward of Tgk Chik Di Tiro Regional Hospital, totaling 212 nurses. The technique for determining the total sample in this study uses the Rule of the Thumb formula with the formula: 5-10 x total indicators so that a total sample of 155 nurses is obtained. The research instrument is a questionnaire on skills in performing bedside handover and patient safety. All question items have been tested for validity and reliability. The data analysis used is descriptive correlation analysis using the chi-square test. The results show that the value in the Pearson chi-square column with Asymptotic Significance is 0.000 <0.05, so it can be concluded that there is a significant relationship between nurses' skills in performing bedside handover and patient safety. It is recommended that hospital management continue to strive to improve the skills of nurses in carrying out bedside handovers so that patient safety increases towards complete health.